Patient-Centered Care in The Digital Era: A Systematic Review of Patient Satisfaction Measures in Virtual Healthcare - Abdelsalam , Eng. Samar Magdy; Rehman, Dr. Asad Ur (International Journal of Basic and Applied Sciences, 2025)
The rapid integration of virtual healthcare technologies has transformed the delivery of patient-centered care, especially in the wake of global ‎health crises. Patient satisfaction is a critical indicator of care quality in digital environments, influenced by accessibility, communication, ‎digital literacy, system usability, and trust. This systematic review aims to evaluate the key determinants of patient satisfaction in virtual ‎healthcare settings, identifying common themes and gaps to inform the development of patient-centered digital care models. A systematic ‎review of 20 peer-reviewed studies was conducted using databases such as PubMed, Scopus, Web of Science, and Google Scholar. Studies ‎employed diverse methodologies, including cross-sectional surveys, systematic reviews, and cohort studies. Data were synthesized using a ‎narrative approach and coded into significant themes. High levels of patient satisfaction were associated with ease of access, strong digital ‎infrastructure, clear communication, and user-friendly platforms. However, satisfaction declined among populations with limited digital ‎literacy or technological access. Trust in data security and continuity of care also emerged as significant contributors. Despite promising ‎outcomes, the lack of standardized satisfaction measurement tools and variability in study designs presented challenges in comparative ‎evaluation. The review highlights that while virtual healthcare holds great promise for enhancing patient satisfaction, it requires inclusive ‎design, secure systems, and personalized care approaches. Standardized assessment frameworks and further research across diverse ‎populations are needed to advance equitable and effective digital health strategies‎.